Correlation of Seizure Increase and COVID-19 Outbreak in Adult Patients with Epilepsy: Findings and Suggestions from a Nationwide Multi-centre Survey in China. (May 2021) - Zeng, Chang; Meng, Hongmei; Zhu, Yulan; Yao, Lifen; Lian, Yajun; Zhu, Yanmei; Zhang, Min; Dai, Yuwei; Wang, Kang; Han, Xiong; Li, Ling; Zhang, Lifang; et al.
Highlights: A minority (8.33%) of PWE experienced seizure worsening during the COVID-19 outbreak. Feeling nervous about the pandemic, poor quality of life, drug reduction/withdrawal, moderate anxiety during the COVID-19 outbreak and non-seizure free before the COVID-19 outbreak were independently related to seizure increase during the epidemic. PWE had a high percentage of depression, anxiety and poor sleep quality during the COVID-19 outbreak, suggesting that special attention should be paid on the mental health of this population. Abstract: Objectives: To investigate the impact of the COVID-19 outbreak on the behaviours, mental health and seizure control of adult patients with epilepsy (PWE) and to identify the correlation of seizure increase and the COVID-19 outbreak to guide the medical care of individuals with epilepsy during a public health crisis. Methods: This study was conducted at 28 centres from February 2020 to April 2020. Participants filled out a 62-item online survey including sociodemographic, COVID-19-related, epilepsy-related and psychological variables and were divided into two groups based on whether their seizure frequency increased during the COVID-19 pandemic. Chi-square tests and t-tests were used to test differences in significant characteristics. Multiple logistic regression analyses were used to identify risk factors for seizure worsening. Results: A total of 1, 237 adult PWE were enrolled for analysis. Of this sample, 31 (8.33%) patients experienced an increase in seizures during the pandemic. Multivariate logistic regression suggested that feeling nervous about the pandemic ( P < 0.05), poor quality of life ( P  = 0.001), drug reduction/withdrawal ( P  = 0.032), moderate anxiety during the COVID-19 outbreak ( P  = 0.046) and non-seizure free before the COVID-19 outbreak ( P < 0.05) were independently related to seizure increase during the pandemic. Conclusions: During the COVID-19 pandemic, PWE with poor quality of life and mental status, as well as AED reduction/withdrawal, were more likely to experience seizure increase. This observation highlights the importance of early identification of the population at high risk of seizure worsening and implementation of preventive strategies during the pandemic.